(untitled) (Architecture Image Studies, 2026)
This study examines electoral success through the lens of Actor-Network Theory (ANT), emphasizing that power in elections is produced not solely by individual candidates or party structures, but through dynamic networks of human and non-human actors. By situating elections within relational configurations involving social ties, technology, institutions, and local values, the study contributes to political network analysis in the context of Indonesia’s open proportional representation system. Using a qualitative case study approach, the research was conducted in Bone Regency, South Sulawesi. Data were collected through in-depth interviews, observations, and document analysis, guided by the ANT principle of “following the actants.” Informants were selected purposively based on their strategic roles within the campaign network. Data analysis involved reduction, display, and verification to ensure analytical rigor and contextual validity. The findings reveal that Yasir Machmud’s electoral victory was shaped by a multi-stage network formation process, including issue mobilization, organizational structuring, integration of social media and technology, adaptive coordination, and final consolidation. Trust-based social relations, cultural values, and digital technologies functioned as interconnected actors that mediated power, mobilization, and voter engagement. Social media, algorithms, and campaign tools operated not merely as instruments, but as active agents influencing political perception and participation. The study concludes that electoral success is the outcome of a complex, adaptive actor network in which human and non-human elements interact structurally, affectively, and symbolically. This research underscores the relevance of ANT for understanding contemporary local electoral politics in Indonesia.